Desvendando a assistência estudantil: as diferenças entre o auxílio estudantil e os serviços de permanência estudantil - Polo, Daniela Brun (2023)
This research has as object of study the Student Aid Program in federal universities, which sought to understand and evaluate the organization, implementation and structuring of this program in federal universities located in the southern region of Brazil, through the information published on the official websites of these federal universities, evidencing the operationalization of student assistance, which deal with responses designed to address the vulnerabilities highlighted by academics. For this purpose, the present research adopts the modality of bibliographical and documentary study, from which it is intended to reflect on some of the contradictions present in the implementation of the public education policy at the higher education level, mainly with regard to student assistance. The methodology proposed for the development of the research has a qualitative character, having as theoretical support the dialectical historical materialist method, being an exploratory and explanatory research. The approach to the theme will seek to critically contextualize social policy, with emphasis on higher education, after the second university reform that took place in the neoliberal context, in order to achieve this objective, higher education will be “divided” between the existing governments after the 2000s. The emphasis of the educational social policy in higher education falls on the student assistance program, which articulates dimensions of public policy on higher education, which expresses one of its contradictions by referring both to the struggles of the student movement and as a strategic part of the capitalist expansion. The source material for the research will be obtained through data collection on the websites of federal universities in the southern region of the country, within which we will seek to identify the actions, programs and student assistance projects that these universities develop, both in terms of refers to “bolsification” as well as other services offered by universities. The effectiveness of the research will be based on documental and bibliographical analysis.